HNO-ärztliche Therapie des Schwindels bei älteren Patienten - Westhofen, Martin (DMW - Deutsche Medizinische Wochenschrift, 2019)
Gait disturbance and risk for falls of the elderly are a major problem for neurotologic diagnosis and treatment. Diagnostic differentiation especially in the case of acute vestibular syndrome and in cases of chronic or recurrent paroxysmal vestibular deficits is mandatory for treatment indications. Criteria for medical, surgical conservative and surgical destructive therapy as well as for vestibular rehabilitation are outlined.
Keywords: Vestibulardiagnostik; plötzlicher Sturz; Gleichgewichtsstörung; Betahistin; vestibuläres System